2023
DOI: 10.1101/2023.09.14.557734
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Critical contribution of mitochondria in the development of cardiomyopathy linked to desmin mutation

Yeranuhi Hovhannisyan,
Zhenlin Li,
Domitille Callon
et al.

Abstract: Beyond the observed alterations in cellular structure and mitochondria, the cellular mechanisms linking genetic mutations to the development of heart failure in patients affected by desmin defects remain unclear due, in part, to the lack of relevant human cardiomyocyte models. We investigated the role of mitochondria using cardiomyocytes derived from human induced pluripotent stem cells carrying the heterozygous DES-E439K desmin mutation, that were either isolated from a patient or generated by gene editing. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 103 publications
(133 reference statements)
0
2
0
Order By: Relevance
“…When studying how the p.E439K desmin variant may affect mitochondria in cardiomyocytes derived from human induced pluripotent stem cells (iPSC‐CMs), Hovhannisyan et al concluded that not only are mitochondria physically altered but also functionally. The study demonstrated fewer cristae that could explain the decrease in the expression of COXIV, a mitochondrial respiratory chain protein (Hovhannisyan et al, 2024). Furthermore, RNA sequencing showed that iPSC‐CMs with the E439K mutation show downregulation of genes that are related to mitochondria, compared to control cells (Hovhannisyan et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When studying how the p.E439K desmin variant may affect mitochondria in cardiomyocytes derived from human induced pluripotent stem cells (iPSC‐CMs), Hovhannisyan et al concluded that not only are mitochondria physically altered but also functionally. The study demonstrated fewer cristae that could explain the decrease in the expression of COXIV, a mitochondrial respiratory chain protein (Hovhannisyan et al, 2024). Furthermore, RNA sequencing showed that iPSC‐CMs with the E439K mutation show downregulation of genes that are related to mitochondria, compared to control cells (Hovhannisyan et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrated fewer cristae that could explain the decrease in the expression of COXIV, a mitochondrial respiratory chain protein (Hovhannisyan et al, 2024). Furthermore, RNA sequencing showed that iPSC‐CMs with the E439K mutation show downregulation of genes that are related to mitochondria, compared to control cells (Hovhannisyan et al, 2024). Mitochondrial alterations in desmin mutant and null cells have been the focus of many studies and reviews suggesting that respiration parameters tend to decrease which can be one explanation for cardiomyocyte dysfunction and altered functionality (Alam et al, 2018; Maggi et al, 2021; Smolina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%